Analysis of collaborative wireless vehicular technologies under realistic conditions. Issue 2 (11th November 2021) - Tahir, Muhammad Naeem; Katz, Marcos; Rashid, Urooj
Abstract: Reliable communications are essential to provide intelligent services to connected cars. For operational services, connected vehicles in VANET (Vehicle Ad hoc Networks) regularly transfer large amounts of data related to vehicular safety. Similarly, V2X (Vehicle‐to‐Everything) communications include vehicles exchanging information with each other and with infrastructure that is, Vehicle‐to‐Infrastructure (V2I) and Vehicle‐to‐Vehicle (V2V). This paper has analyzed the performance of IEEE 802.11p and 5G test network in a collaborative manner under realistic conditions. For performance analysis the exchange of safety‐critical road weather and traffic information has been performed to enhance the traffic safety and traffic efficiency in the domain of intelligent transportation system (ITS). The vehicular connectivity is provided in V2V and V2I scenarios by utilizing short‐range IEEE 802.11 standard or cellular approaches, such as the 5G network. Here, we consider combining these technologies in a cooperative manner to exploit jointly their advantages. In this cooperative heterogeneous network, the IEEE 802.11p supports safety‐related pilot use cases while the provision of non‐safety‐related pilot use cases are supported by the 5G test network. The performance analysis revealed that the IEEE 802.11p performs quite reasonably well with restricted mobility in contrast of 5G test network in a collaborative manner to avoid road accidents.